2020
DOI: 10.1039/d0cp00029a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of resonances and anionic fragments upon electron attachment to benzaldehyde

Abstract: In the present study, we investigated the formation of negative ions following electron attachment to benzaldehyde in the gas-phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The presence of similar resonances below 2 eV suggests that the mentioned anions associated with DEA to SU and OTfU may be formed from the same TNI state of the parent molecule. We note that the presence of a characteristic resonance for O − around 8-9 eV has also been reported in many DEA studies [32][33][34]. In comparison with the literature, Huber et al [35], in their study on hydroxyurea, calculated a similar thermodynamic threshold of 4.57 eV at room temperature (298 K) for the O − formation using the G4(MP2) method.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The presence of similar resonances below 2 eV suggests that the mentioned anions associated with DEA to SU and OTfU may be formed from the same TNI state of the parent molecule. We note that the presence of a characteristic resonance for O − around 8-9 eV has also been reported in many DEA studies [32][33][34]. In comparison with the literature, Huber et al [35], in their study on hydroxyurea, calculated a similar thermodynamic threshold of 4.57 eV at room temperature (298 K) for the O − formation using the G4(MP2) method.…”
Section: Resultssupporting
confidence: 78%
“…In that study, CH3 − was predominantly observed at about 6 eV, while NH − showed a main peak at about 11 eV. Since the experimental data for DMSU were not conclusive, we tried to assign the We note that the presence of a characteristic resonance for O − around 8-9 eV has also been reported in many DEA studies [32][33][34]. In comparison with the literature, Huber et al [35], in their study on hydroxyurea, calculated a similar thermodynamic threshold of 4.57 eV at room temperature (298 K) for the O − formation using the G4(MP2) method.…”
Section: Resultsmentioning
confidence: 97%
“…It was reported that the O – anion is formed at electron energies of 4.4 and 8.3 eV while NH 2 – is observed at 6 eV. Moreover, the recently published work by Ameixa et al 60 on the formation of fragment anions upon electron attachment to benzaldehyde showed the formation of O – via the cleavage of C=O bond in a characteristic resonance between 8 and 9 eV. In our present study, the second resonance position of 8.3 eV is in the same energy range.…”
Section: Resultsmentioning
confidence: 91%
“…It is also worthy to note that in the previous studies of DEA to benzaldehyde, with the C O group similar to that in NA, O − anion generation was also observed at three higher energy (7.8, 8.9, and 10.5 eV) resonances. 59 The m / z = 16 anion was also measured in the investigations of electron capture by acetamide (CH 3 CONH 2 ). 60 Abdoul-Carime et al assigned the ion with m / z = 16 to O − based on earlier observations, which indicated the lack of formation of the NH 2 − ion from the molecules containing the amide group.…”
Section: Resultsmentioning
confidence: 99%